The Evolution of Desire: the evolution of Human mating - Gómez Pignataro, Luis Diego (Universidad de Costa Rica, 1996)
El documento contiene la reseña de los siguientes libros:Ethnobotany. Evolution of a discipline.Palms throughout the World. Smithsonian, Washington,D.C.Asteraceae. Cladistics and ClassificationFlora of the Venezuelan GuayanaMedicinal Mushrooms An exploration of Tradition, Healing and Culture.The Orchid Paintings of Franz BauerHealth and Disease in Developing CountriesA History of the OrchidThe domesticated CapsicumsField Guide to the Palms of the AmericasThe cattleyas and their Relatives.I. The Cattleyas.(1988),II. The Laelias (1990),III. Schomburgkia, Sophronitis, and other South American Genera (1993)Investing in Natural Capital. The ecological economics approach to sustainability.Colombia. Diversidad Biótica.I.Icones Pleurothallidinarum XII. Systematics of Brachionidium.Latin American Insects and EntomologyBiodiversity and Conservation of Neotropical Montane ForestsNeotropical Plant Families: a concise guide to families of vascular plants in the Neotropics.Einstein Lived HereNeotropical Rainforest MammalsLa cucaracha. Un curioso insectoDiccionario de ecología para aficionadosBiodiversidad marina y costera de MéxicoLa Selva: Ecology and natural history of a neotropical rain forestLa vida silvestre en Mesoamérica: Diagnóstico y estrategia para su conservación.Opciones al uso unilateral de plaguicidas en Costa Rica. Pasado, presente y futuro.